Field-measured canopy height may not be as accurate and heritable as believed: evidence from advanced 3D sensing - Jingrong Zang; Shichao Jin; Songyin Zhang; Qing Li; Yue Mu; Ziyu Li; Shaochen Li; Xiao Wang; Yanjun Su; Dong Jiang (Plant Methods, 2023)
Highlights The effects of canopy height, leaf area index, and growth stage on the accurate monitoring of canopy height with different 3D sensors were systematically evaluated. Field-measured canopy height may not be as accurate as believed, especially in the plots with higher canopy height and at later growth stages. 3D sensing methods achieved higher heritable canopy height estimation than field measurement.